2018
DOI: 10.1093/milmed/usx223
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Bioelectrical Impedance Analysis in Estimated Longitudinal Fat-Free Mass Changes in Male Army Cadets

Abstract: The eight general predictive BIA equations used in this study were not found to be valid for analyzing the FFM changes in the Brazilian male army cadets, after a period of approximately 7 mo of military training. Although the BIA equation specific to this population is dependent on the amount of FFM, it appears to be a good alternative to DXA for assessing FFM in Brazilian male army cadets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…Very few studies have previously validated the ability of a whole-body single-frequency BIA to assess changes in body composition over time, compared to DXA. Similar to our findings, previous results show high imprecision of FFM BIA to track changes at the individual level (limits of agreement of ±3e4 kg) compared to DXA, in healthy subjects during loss [22] or gain [23] in FFM. Among obese individuals during weight loss, correlation between change in FFM BIA and FFM DXA was intermediate at r ¼ 0.35, but varied greatly with DXA scanner [22].…”
Section: Discussionsupporting
confidence: 91%
“…Very few studies have previously validated the ability of a whole-body single-frequency BIA to assess changes in body composition over time, compared to DXA. Similar to our findings, previous results show high imprecision of FFM BIA to track changes at the individual level (limits of agreement of ±3e4 kg) compared to DXA, in healthy subjects during loss [22] or gain [23] in FFM. Among obese individuals during weight loss, correlation between change in FFM BIA and FFM DXA was intermediate at r ¼ 0.35, but varied greatly with DXA scanner [22].…”
Section: Discussionsupporting
confidence: 91%
“…We have used BI as the method to assess the BFP in the participants which is a fast, practical, noninvasive, and widely used method. Several studies have validated the use of BI as a standard for body fat estimation [23][24]. BMI is specific for race and hence, we agree to the conclusion of researchers like Piers et al [25], who have concluded that BMI is useful and convenient for population studies but ill-applied in individuals.…”
Section: Discussionsupporting
confidence: 87%
“…PhA was assessed using tetrapolar bioelectrical impedance analysis (BIA), single frequency (50 kHz), model Quantum II (RJL Systems, Detroit, MI, USA), which has been previously validated in adolescents [22]. Participants were instructed to remove all metallic objects before a BIA measurement was taken.…”
Section: Peak Height Velocity (Phv)mentioning
confidence: 99%
“…The reproducibility of the parameters provided by BIA was determined by the coefficient of variation and the technical error of measurement, based on the test-retest method as performed in 23 participants of the study population of an another study [22].…”
Section: Peak Height Velocity (Phv)mentioning
confidence: 99%